The Effect of Accessing Intensity The Brandonkent Everything Youtube Gaming Channel on Subscriber Aggressive Behavior - Koza Pramudya Pratama; Yeni Rosilawati (Universitas Ahmad Dahlan, 2022)
Along with the development of information and communication technology in the era of theÂ Â Â Â industrial revolution 4.0, the need for consuming social media for someone will increase. Youtube is a video provider application, users can search for information, entertainment and viewing. Youtube trends began to spread in Indonesia, many channels emerged and became famous. One of the most well-known YouTubers is Brandont Kent Everything. This study aims to analyze the effect of the intensity of accessing YouTube on aggressive behavior. Subscribers of BrandonKent Everythingâ€™s YouTube gaming channel, with a total sample of 400 respondents, are the population in this study. This research applied the accidental sampling technique. Primary data were collected using a questionnaire tested for validity and reliability. The analysis utilized simple linear regression. Validity test employed confirmatory factor analysis (CFA), and reliability test deployed Cronbachâ€™s Alpha formula using SPSS version 21 for Windows. The t-test obtained a t-count value of 20.020, a regression coefficient (b) of 0.908, and a probability (p) of 0.000. A probability (p) â‰¤ 0.05 implies that the accessing intensity positively and significantly affected aggressive behavior. An ð‘…2 (R Square) of 0.502 or 50.2% indicates that the accessing intensity variable affected the aggressive behavior variable by 50.2 %. The remaining 49.8% was influenced by other variables not examined in this study, such as the surrounding environment, frustration, unpleasant events, awakening, signals of aggression, and group influence. One of the factors that is the reason why the intensity of accessing BrandonKent Everything's Youtube Gaming Channel has an impact on aggressive behavior towards subscribers is that in its content Brandonkent often performs acts of verbal violence such as shouting, saying rudely, cursing. This is what subscribers are watching and likely to be imitated by the audience, especially in this study dominated by students aged 12-16 years where at this age children will actualize themselves to be recognized by their peers.